NUTRITIONAL BEHAVIOR PATTERNS IN PROGRAM OF GIVING ADDITIONAL FOODS FOR INFANTS AGED 0-3 YEARS OF UNDER RED LINE (Universitas Sebelas Maret, 2018)
Malnutrition in the mother and the baby will have impact to health and intelligence, while the child's intelligence ank itself impact to availability of qualified human resources. Weak ability to provide mothers and families parenting will result in even less nutrition incidence of malnutrition in babies. This research aims to: 1) describes the patterns of behavior of nutrients, foster performed the mother on a toddler's bottom is red. 2) supplementary feeding program implementation the recovery on a toddler under the red line. In this study used the theory of George Homans, namely social exchange. This theory rests on the assumption that people engage in behavior to gain rewards or avoid punishment. So that actions taken person is dependent on or punishment is given against such action. This study uses qualitative methods, qualitative, descriptive approach to describe the actual situation on the ground. The selected informer is the mother of a toddler down red lines that receive additional feeding program of recovery, a midwife, dietitian and posyandu cadre clinic. Data collection using in-depth interviews, observation, and documentation. The results showed that: 1) foster nutrition behavior patterns on a toddler under the red line is divided into knowledge include the feeding of pervades, the attitude of care and protection for children, psycho-social and parenting practices that include hygiene and environmental sanitation, health practices and health services search pattern and practice of breastfeeding and complementary feeding of breast milk. 2) Restore additional feeding program awarded to 4 toddler Toddler red down the line, extra food that is given in the form of raw food materials are unisex biscuits. There are constraints in the implementation of the programme including provision of additional food system i.e., a toddler who reluctantly taking Restore additional feeding as well as programs that have not been right on target.